Typification of names in the genus Duranta (Duranteae, Verbenaceae) - Pablo, Moroni; Nataly, O’leary (Phytotaxa, 2016)
During the taxonomic revision of the genus Duranta, seventeen names were identified to need typification. All related herbaria and different literature concerning each name were studied. As a result twelve lectotypes, one epitype and four neotypes are designated here, which will contribute to stabilize the nomenclatural framework of the genus. Notes about typifications are provided.